Incentive mechanism for import substitution of mining equipment - A. A. Grabski; A. A. Rozhkov (Известия высших учебных заведений: Геология и разведка)
Background. The current geopolitical and economic situation makes the task of attaining the technological sovereignty of Russia particularly relevant. This also concerns the need to improve the current investment legislation in the country, including in the field of special investment contracts (SPIC). The SPIC is a form of public–private partnership, which should be primarily aimed at overcoming the technological gap and import dependence through the implementation of a phased import substitution and innovative development of the Russian coal industry and domestic mining machine building.   Aim. To estimate the possibilities of using SPIC as a mechanism to stimulate investment and technological innovation in the process of import substitution of foreign mining equipment in the context of anti-Russian sanctions.   Materials and methods. The research was based on the methods of system analysis, expert evaluation, technological foresight, logical and comparative analysis, economic and statistical processing of information, including its tabular interpretation. The data of coal companies and Rosinformmugol JSC, as well as those retrieved from Internet sources and open-access publications, were used.   Results. The level of import dependence of the Russian coal industry on foreign mining equipment was evaluated. The possibility of using SPIC to stimulate investment and technological innovation in the process of import substitution of foreign mining equipment in the context of anti-Russian sanctions was estimated. The most critical positions in terms of dependence on imported mining equipment supplies were identified; proposals were made for possible sites to attract investors through the SPIC mechanism for localization of key technological mining equipment and components.   Conclusion. The conducted estimation of the possibility of using incentive mechanisms showed SPIC to be an effective mechanism to stimulate the process of import substitution of mining equipment. It should be noted that the current geopolitical and economic situation makes the task of improving investment legislation, which also covers SPIC regulation, particularly important.